Potential molecular markers for estuarine crocodiles (crocodylus porosus) from Sarawak / Ruhana Hassan, Koh Hui Eng and Nur Sara Shahirah Abdullah - Hassan, Ruhana; Koh, Hui Eng; Abdullah, Nur Sara Shahirah (2008)
Crocodylus porosus, estuarine crocodiles, is the most common crocodile that can be found in Sarawak. They inhabit wetlands near river mouths and migrate to upper side of the rivers during breeding season. Crocodiles are important economically as hides fetch high price when they are transferred into fine leathers. For many generations, the Chinese consider crocodiles have traditional medicinal value, besides their aphrodisiac properties. Conflicts between humans and crocodiles exist worldwide, and debates continue on how to sustainably manage the crocodiles. This study is designed to explore the possibility of establishing molecular markers for future rapid identification of Crocodylus porosus from Sarawak. Molecular biological techniques employed during this project were total genomic DNA extraction, Polymerase Chain Reaction (PCR) and PCR-Restriction Fragments Length Polymorphism (PCR-RFLP). Modified CTAB protocol had successfully extracted the total genomic DNA from tissue sample of C. porosus and PCR had successfully amplified the putative Cytochrome b (Cyt b) gene of approximately between 600-700 bp. PCR-RFLP showed that four restriction enzymes (REs) namely Alul, Csp6I, Rsal and Mspl gave restriction profiles, suggesting that they could become molecular markers for C. porosus from Sarawak.